Plant Identification in Traditional Ceremony of Siraman Pengantin in Jombang Regency - Eka Yulia Siti Munawaroh; Mucharommah Sartika Ami (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The purpose of this study was to identify the types of plants used in the Siraman Pengantin in the Jombang Regency. The method used is interviews, direct observation, and literature study. Interviews were conducted with three resource persons who have expertise in the field of Siraman Pengantin in Jombang Regency, to find out the types of plants used in the traditional ceremony. Direct observations were made to identify the morphological structure and classification of each plant species used in the traditional ceremony. The results of identification through direct observation are then compared with a literature study to ensure the classification of plants. The data obtained were analyzed descriptively. The results showed that there were 41 types of plants used in the Siraman Pengantin ceremony in the Jombang Regency. All of these plant species belong to the Angiosperms group. A total of 26 species are dicotyledonous plants and the other 15 species are monocotyledonous plants. The identified dicotyledonous plant families are Achariaceae, Annonaceae, Apiaceae, Clusiaceae, Convolvulaceae, Cucurbitaceae, Euphorbiaceae, Fabaceae, Magnoliaceae, Moraceae, Myrtaceae, Oleaceae, Piperaceae, Rosaceae, Sapotaceae, and Solanaceae. The monocotyledonous plant families identified were Arecaceae, Bromeliaceae, Dioscoreaceae, Liliaceae, Musaceae, Pandanaceae, Poaceae, and Zingiberaceae.